2007
DOI: 10.1007/s00411-007-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of conversion coefficients from measurable to risk quantities for external exposure over contaminated soil by use of physical human phantoms

Abstract: Conversion coefficients from measurable quantities such as air kerma free-in-air or personal dose equivalent to effective dose were determined by phantom experiments. Heterogenic anthropomorphic phantoms representing children of one and five years age, and a Rando phantom representing an adult were exposed in the open field contaminated by different levels of radiocesium in the upper soil layer, in a forest site and inside a wooden house. LiF thermoluminescent (TL) detectors were used inside the phantoms for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…Luminescence measurements can be used to derive the absolute absorbed dose in the ceramic material of interest, but this dose cannot be directly applied when evaluating the cumulative external Chernobyl-related doses to humans because (a) the background (natural) dose cumulated in the material must be subtracted to obtain the accident dose and (b) the accident dose in the ceramic material must be converted to the dose that would have been measured by a point detector located in free air at a reference location (e.g., at a height of 1 m above a large virgin soil plot), which in turn can be used as an input parameter in model calculations of the doses to humans (see, e.g., Jacob and Likhtarev, 1996;Golikov et al, 1999aGolikov et al, ,b, 2002Golikov et al, , 2007. These steps typically include additional quantitative determination of natural and man-made radiation in the environment and inside the ceramic objects, and use several assumptions with respect to modelling of the radiation field patterns within the ceramic and in the environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescence measurements can be used to derive the absolute absorbed dose in the ceramic material of interest, but this dose cannot be directly applied when evaluating the cumulative external Chernobyl-related doses to humans because (a) the background (natural) dose cumulated in the material must be subtracted to obtain the accident dose and (b) the accident dose in the ceramic material must be converted to the dose that would have been measured by a point detector located in free air at a reference location (e.g., at a height of 1 m above a large virgin soil plot), which in turn can be used as an input parameter in model calculations of the doses to humans (see, e.g., Jacob and Likhtarev, 1996;Golikov et al, 1999aGolikov et al, ,b, 2002Golikov et al, , 2007. These steps typically include additional quantitative determination of natural and man-made radiation in the environment and inside the ceramic objects, and use several assumptions with respect to modelling of the radiation field patterns within the ceramic and in the environment.…”
Section: Methodsmentioning
confidence: 99%
“…If we assume a human lives permanently in an unshielded location in the contaminated forest environment, this person would receive an effective cumulative dose from external exposure of Chernobyl origin of 169 mSv for the Novie Bobovichi area, or 154 mSv per 1 MBq m À2 of 137 Cs in the time period 1986e2004 [calculated using a value of 0.71 Sv Gy À1 as the conversion factor for the absorbed dose in air to the effective dose in adults for outdoor locations (Golikov et al, 2007)]. Actual average cumulative effective doses to humans from the forest contamination in the Novie Bobovichi area must vary widely: from less than 1 mSv for those individuals who visit forests on rare occasions, up to about 39 mSv for those foresters who spend up to 2000 h in the forest annually.…”
Section: Effective Dose To Humans Staying In the Forestmentioning
confidence: 99%
“…According to Figure 10 the conversion coefficient between effective dose rate and air kerma rate in rotational invariant irradiation situations concerning naturally occurring radionuclides is around 0.8 Sv Gy -1 , since the mean value of the gamma energy of those is close to 1 MeV. However, Golikov et al (2007) reports a value of 0.71 Sv Gy -1 for adults and 1.05 Sv Gy -1 for a 1-year old child, based on phantom measurements in an environment contaminated with 137 Cs. Since the conversion coefficient is based on the absorbed dose to several organs in the body it will depend on the size of the body (distance from the source and self-shielding) as well as the energy distribution of the photons from the source.…”
Section: Relation Between Air Kerma and Effective Dosementioning
confidence: 97%
“…Conversion coefficients derived from measurements in a contaminated environment have also been reported (e.g. Golikov et al, 2007). The determination of effective dose from air kerma requires detailed knowledge about the energy deposition in the human body, i.e.…”
Section: Relation Between Air Kerma and Effective Dosementioning
confidence: 99%
“…The estimated doses are based on the activity per unit area of 134 Cs and 137 Cs, taking into account the decline of activity due to decay, the loss of activity due to weathering from surfaces and the shielding factor typical for wooden houses. Calculations undertaken for the purpose of this report, using the same methodology used by UNSCEAR [148,267], indicated that the average additional radiation doses in 2012 in large parts of the Intensive Contamination Survey Area (see Section 5.1.2) would have been well below 1 mSv/year.…”
Section: Off-site Remediation Of Areas Affected By the Accidentmentioning
confidence: 99%